Pengaruh Kompres Air Hangat pada Tempat Penyuntikan Terhadap Respon Nyeri pada Bayi Usia 2-4 Bulan Pasca Imunisasi DPT-HB-Hib - Aini, Anisyah Nur; Rachmawan, Ivan; Winarna, Nuristy Brillian Ainindyahsari (WOMB Midwifery Journal, 2024)
Pain after immunization can affect parents' compliance with their children's immunization schedules, while in Indonesia 7.3% of children have not received complete basic immunization. This study aimed to analyze the effect of warm water compress at the injection site on pain response in infants aged 2-4 months post-immunization at Parijatah Kulon Public Health Center in 2024. The study used a pre-experimental one-group method with a cross-sectional approach, involving 69 infants receiving DPT Hb Hib immunization selected through convenience sampling. Pain measurement using NIPS questionnaire and analyzed with Wilcoxon test. Results showed a decrease in moderate pain from 84.1% to 5.8%, an increase in mild pain from 4.3% to 94.2%, and a total elimination of severe pain previously experienced by 11.6% of respondents (p=0.005). Warm water compress proved effective in reducing pain response in infants post-immunization.